Superior mesenteric and renal flow patterns during intra‐aortic counterpulsation. Issue 5 (25th March 2019) - Johnson, Daniel M.; Lozekoot, Pieter; de Jong, Monique; Parise, Orlando; Makhoul, Maged; Matteucci, Francesco; Lucà, Fabiana; Maessen, Jos G.; Gelsomino, Sandro
Abstract : New Findings: What is the central question of this study? Visceral ischaemia is one of the most feared complications during use of an intra‐aortic balloon pump. Using an animal model, we measured the flows at the abdominal level directly and examined flow patterns to enable investigation of flow patterns during the use of the intra‐aortic balloon pump. What is the main finding and its importance? We show that there is a significant balloon‐related reduction in superior mesenteric flow in both early and mid‐diastole. Abstract: A number of previous studies have shown that blood flow in the visceral arteries is altered during intra‐aortic balloon pump (IABP) treatment. We used a porcine model to analyse the pattern of blood flow into the visceral arteries during IABP use. For this purpose, we measured the superior mesenteric, right renal and left renal flows before and during IABP support, using surgically placed flowmeters surrounding these visceral arteries. The superior mesenteric flow significantly decreased in early diastole ( P  < 0.001) and in mid‐diastole ( P  = 0.003  versus early diastole), whereas in late diastole it increased again ( P  < 0.001  versus mid‐diastole). During systole, the flow was not significantly increased compared with late diastole ( P  = 0.51), but it was significantly lower than at baseline (both P  < 0.001). Flows did not differ between right and left kidneys. Perfusion of either kidney did not change significantly in early diastole ( P  > 0.05), whereas it decreased significantly in mid‐diastole ( P  < 0.001), rising dramatically in late diastole ( P  < 0.001) and with an additional slight increase in systole ( P  = 0.054). This study provides important insights into abdominal flows during intra‐aortic pump counterpulsation. Furthermore, it supports the need to rethink the balloon design to avoid visceral ischaemia during circulatory assistance. Abstract :